2018
DOI: 10.1002/jsfa.8972
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, aroma characteristics and volatile compounds of flavorings from enzymatic hydrolyzed rice bran protein concentrate

Abstract: These findings could lead to the creation of desirable aroma characteristics of rice bran protein concentrate by different preparation methods. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Apart from the above-mentioned pyrazines as effective compounds, 2-acetylpyrrole (RI = 1564) and furaneol (RI = 1629), also known as typical Maillard reaction products, have been stated to augment the roasty aroma of peanut oil and nut products (Arsa & Theerakulkait, 2018;Liu et al, 2011;van Gemert, 2011). The average value of 2-acetylpyrrole was 0.91 ± 0.39 mg/kg and the OT in the source was 0.019 mg/kg (Lin et al, 2019); the ratio of concentration/OT value ≈ 48.…”
Section: The Traits Of the Peanut Butters: Univariate Comparisonsmentioning
confidence: 99%
“…Apart from the above-mentioned pyrazines as effective compounds, 2-acetylpyrrole (RI = 1564) and furaneol (RI = 1629), also known as typical Maillard reaction products, have been stated to augment the roasty aroma of peanut oil and nut products (Arsa & Theerakulkait, 2018;Liu et al, 2011;van Gemert, 2011). The average value of 2-acetylpyrrole was 0.91 ± 0.39 mg/kg and the OT in the source was 0.019 mg/kg (Lin et al, 2019); the ratio of concentration/OT value ≈ 48.…”
Section: The Traits Of the Peanut Butters: Univariate Comparisonsmentioning
confidence: 99%
“…The present study showed that acetic acid produced a sour aroma in RB (Table 2). Hexanoic and octanoic acids contributed to sweaty and cheesy aromas (Table 2), while nonanoic acid contributed to greeny and fatty aromas (Table 2) [22,36]. The relative area of acetic acid is seen at higher levels in IPR30 non-fermented and CI fermented RB (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The identified compounds of RB consist of alcohol, alkanes, ketones, and aldehydes [18][19][20]. Hexanal is a common compound in RB that may cause off-odor in RB because of enzyme activity during processing of RB [21,22]. Another report has shown that volatile compounds of black RB consist of aldehyde, alcohol, alkenes, and ketone [21].…”
Section: Introductionmentioning
confidence: 99%
“…The insolubility of gluten keeps the water quality clear, and good digestion can reduce the defecation of aquatic animals and reduce water pollution. Enzymatic hydrolysis of rice protein can produce high-protein nutritious rice flour with protein content of more than 80%, used in baby food, baked goods, breakfast food, snack food, etc [26]. In addition, rice protein is used as a resistance protein, and as a carrier of some drugs, it will play its unique role in medical and veterinary medicine [27].…”
Section: Rice Protein and Its Modification Technologymentioning
confidence: 99%